2017
DOI: 10.1111/rec.12654
|View full text |Cite
|
Sign up to set email alerts
|

Functional flows: an environmental flow regime benefits riparian cottonwoods along the Waterton River, Alberta

Abstract: With drainage from the Waterton‐Glacier International Peace Park, the Waterton River was dammed in 1964 to trap spring flow and permit offstream diversion for irrigation. Field observations in the 1980s indicated some decrepit riparian woodlands suggesting drought stress of the black and narrowleaf cottonwoods (Populus trichocarpa, P. angustifolia) due to insufficient in‐stream flows. Subsequently, an environmental flow regime commenced in 1991 and provided “functional flows,” deliberately regulating in‐stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 49 publications
(97 reference statements)
1
24
0
Order By: Relevance
“…These included peak magnitude flows, spring recession flows, dry season low flows, and wet season initiation flows. Similar flow components have been identified in other seasonal river systems, such as the Waterton River in Canada (Foster, Mahoney, & Rood, ), the Spol River in Switzerland (Robinson, Siebers, & Ortlepp, ), and both inland and coastal rivers in Australia (Koster, Dawson, O'Mahony, Moloney, & Crook, ; Webb, Koster, Stuart, Reich, & Stewardson, ). These functional flow components are likely relevant for other seasonal climates and can provide a starting point for assessment in locations with limited data availability.…”
Section: Quantifying Functional Flow Componentssupporting
confidence: 66%
“…These included peak magnitude flows, spring recession flows, dry season low flows, and wet season initiation flows. Similar flow components have been identified in other seasonal river systems, such as the Waterton River in Canada (Foster, Mahoney, & Rood, ), the Spol River in Switzerland (Robinson, Siebers, & Ortlepp, ), and both inland and coastal rivers in Australia (Koster, Dawson, O'Mahony, Moloney, & Crook, ; Webb, Koster, Stuart, Reich, & Stewardson, ). These functional flow components are likely relevant for other seasonal climates and can provide a starting point for assessment in locations with limited data availability.…”
Section: Quantifying Functional Flow Componentssupporting
confidence: 66%
“…The study included a dendrochronologal approach to assess the timing of establishment of poplars relative to the historical flow patterns. The findings contribute to the understanding of the ecohydrology of riparian woodlands, and are applicable for the prescription of environmental flows along other regulated rivers (Foster, Mahoney, & Rood, 2018; Glenn, Nagler, Shafroth, & Jarchow, 2017; Hall, Rood, & Higgins, 2011; Rood et al, 2003; Shafroth et al, 2017; Shafroth, Auble, Stromberg, & Patten, 1998).…”
Section: Introductionmentioning
confidence: 82%
“…This ideally positions the seeds right along the recently exposed river margin, where the saturated substrate enables imbibition and rapid germination (Bradley & Smith, 1986; Kalischuk et al, 2001; Dixon, 2003). The period of seed maturation and dispersal is generally limited to a few weeks and peaks around mid‐June in southern Alberta, which is the typical interval for the post‐peak river recession (Kalischuk et al, 2001; Karrenberg et al, 2002; Foster et al, 2018; Figure S2). With the Highwood River as the adjacent seed source, the uppermost zones along the LBR would be much more likely to receive poplar seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported values of stomatal conductance for poplars have been shown to be as high as 1000 mmol m −2 s -1 [44,45], which is usually related to low WUE [11,46], and generally reflects the status of poplars as phreatophytes and riparian species that typically grow on moist alluvial soils after floods or other disturbances [20,[47][48][49]. Our study, carried out in a more xeric habitat of north-central Alberta, revealed that stomatal conductance indeed strongly affects intrinsic WUE (negative correlation, Table 2, Figure 1), but the mean values for all tested genotypes (296 mmol m -2 s -1 ) were much lower than reported, which shows adaptive plasticity of our studied clones to water stress conditions.…”
Section: Discussionmentioning
confidence: 99%